1961
DOI: 10.1177/004051756103101205
|View full text |Cite
|
Sign up to set email alerts
|

Fiber Configuration in Sliver and Roving and its Effect on Yarn Quality

Abstract: Fiber configuration in sliver and the incidence of hooks in sliver and rovings have been studied, employing two different techniques. It has been established that during the drafting of sliver at draw frames, trailing hooks are removed preferentially as com pared to leading hooks. The direction of presentation of hooks in the ingoing material (sliver or roving) at the ring frame has been shown to have a considerable effect on yarn strength and evenness. For best results with carded yarn, the majority of hooks … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
17
0

Year Published

1962
1962
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 27 publications
(18 citation statements)
references
References 7 publications
0
17
0
Order By: Relevance
“…Fiber hooks in the card slivers were discovered in 1949 [14] by the Manchester School of workers who later showed r 13] that the level of waste extraction at combers is critically dependent on the number and direction of presentation of hooks to the cop1ber. A few years later it was demonstrated [8,16 that the hooks formed at carding are still present in the finisher sliver and rovings and that carded-yarn quality is significantly affected by the number and direction of presentation of hooks to the ring-frame drafting zone. Simpson et al [17), employing the cutting-ratio technique for estimating the incidence of hooks, found that end breakages at spinning are also sensitive to this factor.…”
Section: Introductionmentioning
confidence: 99%
“…Fiber hooks in the card slivers were discovered in 1949 [14] by the Manchester School of workers who later showed r 13] that the level of waste extraction at combers is critically dependent on the number and direction of presentation of hooks to the cop1ber. A few years later it was demonstrated [8,16 that the hooks formed at carding are still present in the finisher sliver and rovings and that carded-yarn quality is significantly affected by the number and direction of presentation of hooks to the ring-frame drafting zone. Simpson et al [17), employing the cutting-ratio technique for estimating the incidence of hooks, found that end breakages at spinning are also sensitive to this factor.…”
Section: Introductionmentioning
confidence: 99%
“…The increase in draft/doublings increases the span lengths in the sliver. This is mainly due to process of enhanced straightening of hooks and improved orientation at relatively higher draft given at drawframe [8,9]. Table 5 shows that the values of 2.5 %, 50% and 66.7 % SL in finisher sliver are slightly higher than the respective values in breaker sliver.…”
Section: Breaker Slivermentioning
confidence: 97%
“…A similar observation was made when the linear density of the card sliver was increased, keeping a constant cylinder-doffer speed ratio. Garde, Wakandar, and Bhaduri (1961) observed that the most of the fibers in the card slivers were hooked either at one end or at both ends and a large majority of these fibers was hooked at the trailing end. They further found that with successive passage of drawing, the percentage of hooked fibers was reduced and that of fibers without hooks was increased and the reduction of trailing hooks was much greater than the reduction of leading hooks.…”
Section: Introductionmentioning
confidence: 98%